Pengungkapan Esg Dan Efisiensi Investasi Investigasi Peran Kualitas Audit Dan Transformasi Digital Sebagai Variabel Moderasi - Ningsih, Shela Septia; Zaitul; Ilona, Desi (Cattleya Darmaya Fortuna, 2024)
This study examines the impact of environmental, social and governance (ESG) disclosures on investment performance by considering audit quality and digital transformation as moderating variables. Using a purposive sampling method, this research was conducted using a quantitative approach and focused on energy sector companies listed on the Indonesia Stock Exchange (IDX) in 2018-2023. Hypothesis testing was carried out using multiple linear regression. The results showed that environmental and social disclosures positively influence investment efficiency, while governance disclosures have no significant effect. In addition, audit quality is found to negatively influence investment efficiency, while digital transformation has a positive impact. Hence, the effect of ESG disclosure on investment efficiency varies when moderated by audit quality and digital transformation. When moderated by audit quality, environmental disclosures have a negative effect, while social and governance disclosures have no significant impact. On the other hand, when moderated by digital transformation, environmental disclosure has a positive impact, social disclosure has a negative effect, and governance disclosure has no significant effect on investment efficiency. This finding indicates that moderating factors such as audit quality and digital transformation significantly affect investment efficiency.